Intention to get vaccinations against COVID-19 in French healthcare workers during the first pandemic wave: a cross-sectional survey. (February 2021) - Gagneux-Brunon, A.; Detoc, M.; Bruel, S.; Tardy, B.; Rozaire, O.; Frappe, P.; Botelho-Nevers, E.
Summary: Background: Healthcare workers (HCWs) are at the frontline of the COVID-19 pandemic and identified as a priority target group for COVID-19 vaccines. We aimed to determine COVID-19 vaccine acceptance rate in HCWs in France. Methods: We conducted an anonymous survey from 26 th March to 2 nd July 2020. The primary endpoint was the intention to get vaccinated against COVID-19 if a vaccine was available. Results: Two-thousand and forty-seven HCWs answered the survey; women accounted for 74% of respondents. Among respondents, 1.554 (76.9%, 95% confidence interval 75.1–78.9) would accept a COVID-19 vaccine. Older age, male gender, fear about COVID-19, individual perceived risk and flu vaccination during previous season were associated with hypothetical COVID-19 vaccine acceptance. Nurses and assistant nurses were less prone to accept vaccination against COVID-19 than physicians. Vaccine hesitancy was associated with a decrease in COVID-19 vaccine acceptance. Flu vaccine rate was 57.3% during the previous season, and 54.6% of the respondents had the intention to get a flu vaccine during the next season. Conclusions: Intention to get vaccinated against COVID-19 reached 75% in HCWs with discrepancies between occupational categories. COVID-19 pandemic had no positive effect on flu vaccine acceptance rate.